2014
DOI: 10.1590/0001-3765201420130105
|View full text |Cite
|
Sign up to set email alerts
|

Structure, histochemistry and phytochemical profile of the bark of the sobol and aerial stem of Tontelea micrantha (Celastraceae - Hippocrateoideae)

Abstract: The bark of the underground stem of Tontelea micrantha (Mart. ex. Schult.) A. C. Sm., a native Brazilian Cerrado species, is used in folk medicine for treating kidney ailments. The structures of the underground and the aerial stems were examined and their barks were analyzed for the presence of secondary metabolites. Bark fragments were processed according to conventional techniques in plant anatomy and their chemical compositions examined using histochemical and phytochemical tests, thin layer chromatography,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Cells containing phenolic compounds are common in Maytenus species (Gupta & Sharma 2012) and have also been reported for other genera of Celastraceae (Mercadante-Simões et al 2014). The secondary metabolites are responsible for the relation of the plant with the biotic and abiotic environment.…”
Section: Discussionmentioning
confidence: 63%
“…Cells containing phenolic compounds are common in Maytenus species (Gupta & Sharma 2012) and have also been reported for other genera of Celastraceae (Mercadante-Simões et al 2014). The secondary metabolites are responsible for the relation of the plant with the biotic and abiotic environment.…”
Section: Discussionmentioning
confidence: 63%
“…Histochemical localization studies allows a quick and cost effective method for the preliminary evaluation of plant species in search of new pharmaceuticals. [36][37][38][39] The tissues of phloem parenchyma was found to be the main localising region of various phytoconstituents in G. tiliifolia bark.…”
Section: Discussionmentioning
confidence: 99%
“…16 The acidity, aldehyde and ketone tests were reproduced according to the procedures suggested by Cruz and Galhardo. 17 The verification of reducing sugars was done using the methodology described by Beserra et al 18 and the thin layer chromatography (TLC) technique reported by Mercadante-Simões et al 19 with modifications.…”
Section: Andmentioning
confidence: 99%